2005
DOI: 10.1007/s10620-005-3054-2
|View full text |Cite
|
Sign up to set email alerts
|

Gastroduodenal Crohn's Disease Is Associated With NOD2/CARD15Gene Polymorphisms, Particularly L1007PHomozygosity

Abstract: Limited data exist on the specific association between gastroduodenal Crohn's disease (GDCD) and NOD2/CARD15 gene polymorphisms. The aim of this study was to assess the association between NOD2 polymorphisms and GDCD, and to assess the specific association between each of the 3 major allelic variants G908R, L1007P, and R702W and the clinical features of Crohn's disease. We retrospectively reviewed the records of 202 patients with confirmed Crohn's disease and complete data was performed. Seventy-one patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
1
16
1
Order By: Relevance
“…This is in contrast to a recent study that demonstrated that patients with gastroduodenal CD involvement were more likely to carry 2 allelic CARD15 variants and to be homozygous for the 1007fs mutation. 37 In contrast, in our study CARD15 1007fs homozygotes were overrepresented among MIF GC heterozygous carriers, the group with the lowest upper GI involvement (11.1% compared to 2.7% with the MIF wildtype GG genotype; P ϭ 0.035). However, the observed lack of upper GI involvement was independent of the CARD15 genotype since there was no significant difference in the frequency of upper GI involvement between carriers and noncarriers of CARD15 variants in the GC heterozygous group (P ϭ 0.585).…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…This is in contrast to a recent study that demonstrated that patients with gastroduodenal CD involvement were more likely to carry 2 allelic CARD15 variants and to be homozygous for the 1007fs mutation. 37 In contrast, in our study CARD15 1007fs homozygotes were overrepresented among MIF GC heterozygous carriers, the group with the lowest upper GI involvement (11.1% compared to 2.7% with the MIF wildtype GG genotype; P ϭ 0.035). However, the observed lack of upper GI involvement was independent of the CARD15 genotype since there was no significant difference in the frequency of upper GI involvement between carriers and noncarriers of CARD15 variants in the GC heterozygous group (P ϭ 0.585).…”
Section: Discussioncontrasting
confidence: 83%
“…However, the observed lack of upper GI involvement was independent of the CARD15 genotype since there was no significant difference in the frequency of upper GI involvement between carriers and noncarriers of CARD15 variants in the GC heterozygous group (P ϭ 0.585). Similar to our study, the analysis by Mardini et al 37 was performed retrospectively. To avoid selection and ascertainment biases, we therefore prospectively analyzed the MIF and CARD15 genotype status of all 13 CD patients diagnosed To compare expression levels between inflamed and noninflamed colonic lesions, mRNA expression in noninflamed tissue was arbitrarily set to 1.0.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…[29][30][31][32][33][34][35] All samples were analyzed in one laboratory (Dr de Villiers, University of Kentucky Medical Center). For NOD2, the allelic variants G908R, L1007P, and R702W were assayed by polymerase chain reaction (PCR), amplification of the entire sequence of exon 8 and exon 11, and the relevant segment of the large exon 4 of the NOD2/CARD15 gene, followed by restriction fragment length polymorphism analysis.…”
Section: Genetic Testingmentioning
confidence: 99%
“…They frequently need a surgical intervention and have a high risk of restenosis. This mutation is also associated with gastroduodenal involvement (26)(27)(28). In addition to CD, three missense mutations (R334W, R334QQ an L469F) in the nucleotide-binding domain of Nod2 confer susceptibility to another granulomatous disorder affecting the eyes, skin, and joints known as Blau syndrome (29) and early onset sarcoidosis (30).…”
Section: Genetic Factorsmentioning
confidence: 99%